2021
DOI: 10.3390/w13030368
|View full text |Cite
|
Sign up to set email alerts
|

Damage Characteristics and Mechanism of the 2017 Groundwater Inrush Accident That Occurred at Dongyu Coalmine in Taiyuan, Shanxi, China

Abstract: On 22 May 2017, a groundwater inrush accident occurred in the gob area of coal floor at Dongyu Coal Mine in Qingxu County, Shanxi Province, China. The water inrush accident caused great damage, among which six people died and the direct economic loss was about CNY 5.05 million. An elliptical permeable passage appeared at the floor of the water inrush point, and the lithology of the outburst is mainly fragmented sandy mudstone and siltstone of coal roof No.2 in the lower layer of coal seam No.3, which is curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Weakly cemented soft rock, such as carbonaceous mudstone, mudstone, and silty mudstone, is distributed widely in the top and floor of coal seams in central and western China under the influence of geological tectonics [1][2][3][4]. Because the low strength, loose cementation, and poor performance of this rock, especially water, will result in softening and expansion, it is always sustainable growth and serious deformation of surrounding rock when tunneling in weak cemented soft rock roadway, drenched by water, leading to some accidents, including the floor heave, roof caving, and collapse, which seriously restrains efficient coal mine production safety [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Weakly cemented soft rock, such as carbonaceous mudstone, mudstone, and silty mudstone, is distributed widely in the top and floor of coal seams in central and western China under the influence of geological tectonics [1][2][3][4]. Because the low strength, loose cementation, and poor performance of this rock, especially water, will result in softening and expansion, it is always sustainable growth and serious deformation of surrounding rock when tunneling in weak cemented soft rock roadway, drenched by water, leading to some accidents, including the floor heave, roof caving, and collapse, which seriously restrains efficient coal mine production safety [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Stopping drainage inevitably leads to a rise in the underground water level of the mine and forming goaf water [6,7]. Studies have shown that goaf water not only becomes a potential water hazard when the mine is in operation [8], but also becomes a contamination source of regional groundwater after the mine is closed [9,10]. Due to the influence of mining activities, the underground mining area becomes a gathering place for groundwater in the mining area, and also is a place where physical, chemical, and biological pollution of groundwater occurs [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The mine water inrush is ferocious, often engulfing the roadway in an instant and resulting in considerable casualties and economic losses. A total amount of 779 water disasters happened in China, which resulted in enormous casualties (3,831 deaths) and economic losses in the period 2000-2020 [2]. After a water inrush disaster occurs in mine production processing, it is urgent to identify the source of water inrush and formulate the corresponding control measures, and varied control measures should be made out for the different aquifer conditions based on water richness.…”
Section: Introductionmentioning
confidence: 99%